Evaluation of different scoring systems for repeating Transarterial Chemoembolization in Egyptian patients with Hepatocellular Carcinoma - Alhaddad Omkolsoum; Gomaa Asmaa; Shamandy Merhan El; Kohla Mohamed; Edrees Ahmed; Ashour Reham (Romanian Journal of Internal Medicine)
Hepatocellular carcinoma (HCC) patients undergoing transarterial chemoembolization (TACE) have a diverse range of outcomes due to their high degree of heterogeneity. Therefore, different predictive scoring systems have been created to assist in decision-making regarding retreatment with TACE. We compared the predictive capabilities of different scoring systems, such as ART, ABCR, and SNACOR, for prediction of the outcome of subsequent TACE in HCC patients.